Comparison Analysis of Patient’s Satisfaction Towards Dental Treatment by Dental Co-Ass Students and Dentist Practitioner on RSGMP Jenderal Soedirman University - Shabrina Nur Zahra Setiawati; Refius Pradipta Setyanto; Joko Mulyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
User satisfaction in a health system is defined as the way the person perceived the service and its judgements about the care received. In Indonesia, health provider who could give dental treatments are Dentist, Dental Specialist, and Dental Co-ass Students under the supervision of Dentist in Charge of Service (DPJP) and under applicable laws and regulations. The objective of this research was to analyze whether there was a significant difference between patient’s satisfaction towards dental and oral treatment by dental co-ass students and dentist practitioner on RSGMP Jendreral Soedirman University, and measured using the Patient Satisfaction Questionnaire-18 (PSQ-18) that was modified according to field condition. Hypothesis of this research was there was a significant difference between patient satisfaction who received dental and oral treatment by co-ass students and dentist practitioner on RSGMP Jenderal Soedirman University. Result show that patient received treatment from general dentist showed higher level of satisfaction compared to patient received treatment from dental co-ass. The management of RSGMP Universitas jenderal Soedirman as a service provider needs to evaluate aspects which are still lacking in order to improve the quality of health services. Further research is needed to compare between patient satisfaction at RSGMP Universitas Jenderal Soedirman and patient satisfaction at other hospitals.